Polyarylester nanofiber and preparation method thereof
Through copolymerization and blending melt spinning technology, combined with deprotonation and etching treatment of the DMSO-KOH system, blended liquid crystal polyaryl (LCP) nanofibers with small diameter and controllable length-to-diameter ratio were successfully prepared, which solved the problem of difficulty in achieving large-scale continuous production in the existing technology and achieved efficient preparation of nanofibers.
Patent Information
- Application Number
- CN202510295432.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-13
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-03-13
AI Technical Summary
It is difficult to prepare blended liquid crystal polyaryl (LCP) nanofibers with small diameters and controllable length-to-diameter ratios in the prior art, and it is difficult to achieve large-scale continuous production by traditional methods.
By copolymerizing the acetylated 4-hydroxybenzoic acid (HBA), 6-hydroxy-2 naphthoic acid (HNA) with 4-hydroxybutyric acid (GHB), HBA/GHB/HNA copolymerization LCP and HBA/HNA copolymerization LCP were obtained, which were used as pellet B and pellet A, respectively, and blended and melt spinning were performed. Blend LCP nanofibers were prepared by deprotonation and etching treatment of the DMSO-KOH system.
It is realized that blended LCP nanofibers with small diameter and controllable length and diameter ratios are prepared, and this method is suitable for large-scale continuous production. The diameter and length of the nanofibers can be controlled by regulating the amount of GHB added and the mass proportion during spinning.
Smart Images

Figure CN119777032A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nanofibers and relates to a method for preparing polyarylate nanofibers. Background Art
[0002] Liquid Crystal Polyarylate (LCP) is a type of high-performance material with liquid crystal properties. Its excellent mechanical properties, heat resistance, chemical resistance and dimensional stability make it widely used in various fields. The molecular chains inside LCP are highly regular and can form a liquid crystal phase after heating. The molecular chains can be arranged in order during the flow process, thereby forming a highly oriented structure. Therefore, when LCP is melt-spun at high speed, under the high shear rate of the spinneret, the LCP molecular chains are arranged in order along the spinning direction with the melt and flow at high speed. After being spun into LCP fibers, the molecular chains are arranged in order along the fiber axis to form anisotropy, which is shear-induced orientation. Therefore, the binding force along the fiber axis is dominated by the chemical bonds in the molecular chain, so the binding force is strong, while the weaker binding forces such as intermolecular forces and van der Waals forces are dominant along the fiber radial direction, resulting in a large difference in the binding force in each direction inside the LCP fiber. Inspired by the preparation of aramid nanofibers by etching aramid nanofibers, dimethyl sulfoxide (DMSO)-potassium hydroxide (KOH) removes the proton H in the -CONH- in the molecular chain with KOH, making the N atom negatively charged. The negative charges repel each other, increasing the distance between the molecular chains, and achieving the purpose of disassembly along the fiber axis. At the same time, the system will also etch the amorphous part of the fiber, destroying the weak binding force along the radial direction of the fiber, such as van der Waals force, hydrogen bond, π-π interaction, etc., retaining the strong chemical bonding force in the crystalline part and along the axial direction of the fiber, so that nano-scale aramid fibers are obtained "from top to bottom". Therefore, we use this etching method to treat polyarylate fibers in order to obtain polyarylate nanofibers. Summary of the invention
[0003] The purpose of the present invention is to prepare a blended LCP nanofiber with a small and uniform diameter, a numerically controllable aspect ratio, and large-scale continuous production.
[0004] In order to achieve the above object, the present invention provides a preparation scheme of blended LCP nanofibers: (1) Copolymerizing acetylated 4-hydroxybenzoic acid (HBA), 6-hydroxy-2-naphthoic acid (HNA), and 4-hydroxybutyric acid (GHB) to obtain HBA / GHB / HNA copolymerized LCP (pellet B); copolymerizing acetylated HBA and HNA to obtain HBA / HNA copolymerized LCP (pellet A); (2) melt spinning the pellets A and B in step (1), respectively melting them through single screw extruder A and single screw extruder B, metering and conveying them through matching function CNC metering pumps A and metering pumps B, and conveying melt A and melt B to a static mixer with a certain mass ratio, and after being fully mixed, extruding through a spinneret to obtain a blended LCP fiber; (3) placing the fibers spun in step (2) into dimethyl sulfoxide (DMSO), adding potassium hydroxide (KOH) solid, and stirring at a certain temperature for a certain time to obtain a blended LCP nanofiber suspension; (4) The suspension obtained in step (3) is filtered, washed with deionized water, and then placed in an oven for drying to finally obtain blended LCP nanofibers.
[0005] Preferably, the mass ratio of the components in the pellet B of step (1) is HBA: HNA: GHB = 70: 30: (1-5), and more preferably HBA: HNA: GHB = 70: 30: 5; the mass ratio of the components in the pellet A is HBA: HNA = 7: 3.
[0006] As a preferred embodiment, in step (2), the speed N of the metering pump A is A Satisfies the functional relationship N with time t A = sin [π(t-15) / 30] + 9 + 2k, speed N of metering pump B B Satisfies the functional relationship N with time t B = N - N A = -sin [π(t-15) / 30] +11 – 2k, t is the real time in seconds, and the period of both functions is 60 s. The k value determines the speed range and the k value of both functions is the same, ranging from 1 to 3.
[0007] As a preferred method, the mass ratio of the two granules is N B and N A Directly controlled and constantly changing, the calculation formula is: mass proportion of pellet A or B = (N A or N B / N)×100%. k is 1-3, corresponding to N A and N B The total range is 10-16 rpm and 10-4 rpm, and the corresponding mass proportions of pellet A and pellet B are 50%-80% and 50%-20% respectively, and the sum of the speeds at the same time is the total speed N, which is constant at 20 rpm, that is, N = 20 rpm = N A + N B , the sum of the mass proportions of the two corresponding pellets is constant at 100%.
[0008] Preferably, in step (2), the temperatures of the four zones of the two groups of single screw extruders for melt blending spinning are 250°C, 280°C, 300°C, and 320°C, respectively, the screw speed is 90 rpm, and the shear rate at the spinneret is 2000 s -1 , the winding speed of the winder is 300 rpm and the reciprocating axis frequency is 200 Hz.
[0009] Preferably, in step (3), the corresponding relationship between the fiber and the DMSO-KOH etching system is 150 mL DMSO and 1 g KOH solid for every 2 g of fiber, the temperature is 30° C., and the stirring time is 10 days.
[0010] Compared with the prior art, the present invention has the following positive and beneficial effects: (1) Based on the existing traditional process of preparing HBA / HNA copolymer LCP pellets A by polymerizing HBA and HNA, the present invention adds GHB monomer to the polymerization system to obtain a copolymer LCP containing a small amount of -CH2- structure in the main chain, namely HBA / GHB / HNA copolymer LCP pellets B. The mass ratio of each component in pellet A is HBA:HNA = 7:3, and the mass ratio of each component in pellet B is HBA:HNA:GHB = 70:30:(1-5).
[0011] (2) The present invention blends two kinds of pellets for melt spinning, such as Figure 1 The difference is that pellet A and pellet B are melted by single screw extruder A and single screw extruder B respectively, and are metered and transported by matching function CNC metering pump A and metering pump B. Melt A and melt B are transported to the static mixer with a certain mass ratio, and are fully mixed and extruded through the spinneret to obtain the blended LCP fiber. The speed of the two groups of metering pumps through the function CNC changes continuously with the change of time seconds. The metering pump speed N A and N B Satisfy the functional relationship N A = sin [π(t-15) / 30] + 9 + 2k and N B = N - N A = -sin [π(t-15) / 30] + 11 – 2k, k value determines the speed range, the value is 1-3, and the value is the same in the two functions, t is the real time in seconds, and the period of both functions is 60 s. For details, see Figure 2 and Table 1, for example, when k = 1, N A Range 10-12 rpm, N BThe range is 10-8 rpm. Specifically, when the time is 18:31:45, t = 45 s, N A = sin [π(45-15) / 30] + 9 + 2 = 11 rpm, N B = 20 - N A = -sin [π(45-15) / 30] + 11 - 2 = 9 rpm.
[0012] (3) In the blended LCP fiber obtained by the present invention, the mass proportion of pellet A and pellet B is N A and N B And k value is directly controlled, and the calculation formula is: mass proportion of pellet A or B = (N A or N B / N)×100%, so k is 1-3, corresponding to N A The total range is 10-16 rpm, corresponding to the total range of pellet A of 50%-80%, corresponding to N B The total range is 10-4 rpm, corresponding to the total range of pellet B is 50%-20%, and the sum of the speeds at the same time is the total speed N constant at 20 rpm, that is, N = 20 rpm = N A + N B , the sum of the mass proportions of the two corresponding particles is constant at 100%. For example, N A = 12 rpm, total speed N = 20 rpm, then N B = 20 –12 = 8 rpm, at this time, the mass proportion of pellet A = (12 rpm / 20 rpm)×100% = 60%, and the mass proportion of pellet B = (8rpm / 20 rpm)×100% = 40%. Therefore, as the spinning process proceeds, the mass proportion of pellets A and B in the obtained blended LCP fiber changes continuously within a certain range.
[0013] (4) In the blended LCP fiber prepared by the present invention, due to the different structures of the two pellets - pellet B contains a small amount of -CH2- structure while pellet A does not, the fiber obtained by the blended spinning of the two pellets is prone to phase separation. This is conducive to the DMSO-KOH system to penetrate deeply into the fiber and deepen the etching of the amorphous region, and is also conducive to the deprotonation of the molecular chain by the system to prepare nanofibers.
[0014] (5) The preparation idea of the present invention is to destroy the weak radial bonding force of the blended LCP fiber and retain the strong axial bonding force by combining deprotonation and etching of the amorphous region, and then disassemble the blended LCP nanofiber "from top to bottom" to obtain the blended LCP nanofiber. When LCP is melt-spun at high speed, the high speed difference between the spinneret and the flowing melt brings about a high shear rate, and the liquid crystal molecular chains of LCP are arranged in an orderly manner along the high-speed flow direction of the melt, which is shear-induced orientation. After cooling, the LCP molecular chains maintain an orderly arrangement along the axial direction of the fiber, and the high degree of orientation will induce an increase in crystallinity, so a highly crystalline anisotropic structure is formed inside the blended LCP fiber. The bonding force along the axial direction of the fiber is dominated by the chemical bonds in the molecular chain, so the bonding force is strong, while the weaker bonding forces such as intermolecular forces and van der Waals forces are dominant along the radial direction of the fiber, resulting in a large difference in the bonding force in each direction inside the blended LCP fiber.
[0015] (6) For the conventional HBA / HNA copolymerized LCP (granule A), there is no proton H in the molecular structure, and KOH can only etch away the amorphous region in the LCP fiber, but cannot achieve the purpose of deprotonation. Therefore, the diameter and length range of the LCP nanofibers prepared by etching are large, and the size is uneven and unstable and cannot be controlled, and even only LCP microfibers can be obtained. In the blended LCP fibers (granules A and B) prepared by the present invention, due to the introduction of GHB repeating units, the -CH2- structure in the main chain increases, and the deprotonation of the ester bond -COO- in the HBA / HNA copolymerized LCP is easier, and the obtained nanofibers have a finer diameter and a more uniform size. Therefore, the blended LCP fibers are easier to prepare nanofibers by the top-down disassembly method. Moreover, the -CH2- structure is easier to be etched off by the DMSO-KOH system than the ester bond -COO-, so the obtained nanofibers are shorter in length. The blended LCP fibers obtained by the above-mentioned melt spinning method have components that change along the fiber direction - the mass proportions of pellets A and pellets B vary between 50%-80% and 50%-20%. Therefore, when fibers with different mass proportions are etched in the DMSO-KOH system, the lengths of the obtained nanofibers are also different, that is, the aspect ratio is controllable. For example, when the mass proportion of a certain section of the fiber is 70-80% pellet A and 30-20% pellet B, since the proportion of pellet B is relatively small, the DMSO-KOH system deprotonates the -CH2- structure less, so the obtained nanofiber length is longer. On the contrary, if the mass proportion of a certain section of the fiber is 50-60% pellet A and 50-40% pellet B, the obtained nanofiber length is relatively short.
[0016] (7) The diameter of the blended LCP nanofibers obtained by the present invention can be regulated by the amount of GHB added during copolymerization. When the amount of GHB added is large, the -CH2- content in the main chain is large. Under the influence of the electron-withdrawing induction effect of the carbon-oxygen double bond C=O, the proton H is easily deprotonated by the DMSO-KOH system, so the diameter of the obtained nanofibers is small. Therefore, the aspect ratio of the nanofibers can be controlled by the mass proportion of the two granules and the amount of GHB added, and the blended LCP nanofibers with both large and small aspect ratios are obtained. The specific control of the aspect ratio of the nanofibers is given by the following example. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 Schematic diagram of the blending spinning of pellets A and pellets B.
[0018] Figure 2 The speed N of the metering pump in Example 1-7 A and N B Graph of the function relationship with time t.
[0019] Figure 3 ① is the acetylation reaction formula of HBA and HNA; ② is the reaction formula of copolymerization of acetylated HBA, HNA and GHB to obtain HBA / GHB / HNA copolymer LCP pellets B and copolymerization of acetylated HBA and HNA to obtain HBA / HNA copolymer LCP pellets A.
[0020] Figure 4 Field emission scanning electron microscope (FESEM) images of the surface and cross section of the blended LCP fibers.
[0021] Figure 5 FESEM photos of the blended LCP nanofibers prepared in Control Example, Example 3, Example 5 and Example 7. DETAILED DESCRIPTION
[0022] Example common steps: Take two monomers HBA and HNA at a mass ratio of 7:3, mix them with acetic anhydride, react at 140°C for 4 h to acetylate the hydroxyl groups of the two monomers, and obtain acetylated HBA and acetylated HNA. Without adding GHB monomer, only the obtained acetylated HBA and acetylated HNA are added into the reactor for polymerization, slowly heated to 300°C, reacted for 8 h under nitrogen atmosphere and kept at 350°C for 1 h to increase the degree of polymerization and ensure uniform molecular weight, wherein the by-product acetic acid is continuously evaporated through the condenser. After the reaction, pellet A is obtained.
[0023] In addition, three monomers, HBA, HNA and GHB, are taken at a mass ratio of 70:30:(1-5), and HBA and HNA are subjected to the above acetylation step to obtain acetylated HBA and acetylated HNA. Then the two monomers are added to a reactor together with the GHB monomer for copolymerization, and the polymerization conditions are the same as above. After the reaction is completed, HBA / GHB / HNA copolymer LCP introduced with GHB repeating units is obtained, namely, pellet B. The specific mass ratios of HBA, HNA and GHB are illustrated in the following examples.
[0024] Comparison Example The pellet A is melt-spun to obtain HBA / HNA copolymerized LCP fibers. During spinning, only single screw extruder A and metering pump A are used. A = N = 20 rpm, the fiber was obtained by spinning 100% pellet A, without pellet B, i.e. without -CH2- structure. Take 2 g of the fiber sample, put it into 150 mL DMSO solution, add 1 g KOH solid, stir at 30 ° C for 10 days, and obtain nanofiber suspension. After filtration, washing and drying, HBA / HNA copolymer LCP nanofibers with a diameter range of 1-15 μm, a length range of 100-500 μm, and an aspect ratio range of 50-100 are obtained.
[0025] Example 1 HBA, HNA and GHB are copolymerized in a mass ratio of 70:30:1 to obtain pellet B. Pellets A and B are mixed and melt-spun to obtain blended LCP fibers. In order to ensure that the mass proportions of pellets A and B in this example are 50-60% and 50-40%, k = 1, N A = sin [π(t-15) / 30] + 11, N A Maintain at 10-12 rpm, N B = 20 -N A = -sin [π(t-15) / 30] + 9, N B The corresponding speed is 10-8 rpm, and the total speed N is constant at 20 rpm at the same time, with a cycle of 60 s. Take 2 g of the fiber sample, place it in 150 mL of DMSO solution, add 1 g of KOH solid, and stir at 30 ° C for 10 days to obtain a nanofiber suspension. After filtration, washing, and drying, the blended LCP nanofibers are obtained with a diameter range of 200-500 nm, a length range of 5-30 μm, and an aspect ratio range of 30-100. Compared with the control example, the diameter and length of this example are significantly reduced by introducing the GHB repeating unit, but the aspect ratio does not change significantly.
[0026] Example 2 HBA, HNA and GHB are copolymerized in a mass ratio of 70:30:2 to obtain pellet B. Pellets A and B are mixed and melt-spun to obtain blended LCP fibers. In order to ensure that the mass proportions of pellets A and B in this example are 50-60% and 50-40%, k = 1, N A = sin [π(t-15) / 30] + 11, N A Maintain at 10-12 rpm, N B = 20 -N A = -sin [π(t-15) / 30] + 9, N B The corresponding speed is 10-8 rpm, and the total speed N is constant at 20 rpm at the same time, with a cycle of 60 s. Take 2 g of the fiber sample, place it in 150 mL of DMSO solution, add 1 g of KOH solid, and stir at 30 ° C for 10 days to obtain a nanofiber suspension. After filtration, washing, and drying, blended LCP nanofibers are obtained with a diameter range of 100-500 nm, a length range of 5-30 μm, and an aspect ratio range of 30-200. Compared with the control example, the introduction of GHB repeating units significantly reduced the diameter and length of this example, but the aspect ratio increased slightly. Compared with Example 1, the content of GHB repeating units was increased, the diameter of this example decreased, and the aspect ratio increased slightly.
[0027] Example 3 HBA, HNA and GHB were copolymerized in a mass ratio of 70:30:3 to obtain pellet B. Pellets A and B were mixed and melt-spun to obtain blended LCP fibers. In order to ensure that the mass proportions of pellets A and B in this example are 50-60% and 50-40%, k = 1, N A = sin [π(t-15) / 30] + 11, N A Maintain at 10-12 rpm, N B = 20 -N A = -sin [π(t-15) / 30] + 9, N BThe corresponding speed is 10-8 rpm, and the total speed N is constant at 20 rpm at the same time, with a cycle of 60 s. Take 2 g of the fiber sample, place it in 150 mL of DMSO solution, add 1 g of KOH solid, and stir at 30 ° C for 10 days to obtain a nanofiber suspension. After filtration, washing, and drying, blended LCP nanofibers are obtained with a diameter range of 50-200 nm, a length range of 5-30 μm, and an aspect ratio range of 50-400. Compared with the control example, the introduction of GHB repeating units significantly reduced the diameter and length of this example, and significantly increased the aspect ratio. Compared with Example 2, the diameter of this example is significantly reduced, and the aspect ratio is significantly increased.
[0028] Example 4 HBA, HNA and GHB were copolymerized in a mass ratio of 70:30:4 to obtain pellet B. Pellets A and B were mixed and melt-spun to obtain blended LCP fibers. In order to ensure that the mass proportions of pellets A and B in this example are 50-60% and 50-40%, k = 1, N A = sin [π(t-15) / 30] + 11, N A Maintain at 10-12 rpm, N B = 20 -N A = -sin [π(t-15) / 30] + 9, N B The corresponding speed is 10-8 rpm, and the total speed N is constant at 20 rpm at the same time, with a cycle of 60 s. Take 2 g of the fiber sample, place it in 150 mL of DMSO solution, add 1 g of KOH solid, and stir at 30 ° C for 10 days to obtain a nanofiber suspension. After filtration, washing, and drying, blended LCP nanofibers are obtained with a diameter range of 50-200 nm, a length range of 5-30 μm, and an aspect ratio range of 70-500. Compared with the control example, the introduction of GHB repeating units significantly reduced the diameter and length of this example, and significantly increased the aspect ratio. Compared with Example 3, the diameter of this example did not change significantly, and the aspect ratio increased slightly.
[0029] Example 5 HBA, HNA and GHB were copolymerized in a mass ratio of 70:30:5 to obtain pellet B. Pellets A and B were mixed and melt-spun to obtain blended LCP fibers. In order to ensure that the mass proportions of pellets A and B in this example are 50-60% and 50-40%, k = 1, N A = sin [π(t-15) / 30] + 11, N A Maintain at 10-12 rpm, N B = 20 -N A= -sin [π(t-15) / 30] + 9, N B The corresponding speed is 10-8 rpm, and the total speed N is constant at 20 rpm at the same time, with a cycle of 60 s. Take 2 g of the fiber sample, place it in 150 mL of DMSO solution, add 1 g of KOH solid, and stir at 30 ° C for 10 days to obtain a nanofiber suspension. After filtration, washing, and drying, blended LCP nanofibers are obtained with a diameter range of 50-70nm, a length range of 5-30 μm, and an aspect ratio range of 100-500. Compared with the control example, the introduction of GHB repeating units significantly reduced the diameter and length of this example, and significantly increased the aspect ratio. Compared with Example 4, the diameter of this example is significantly reduced, and the aspect ratio is slightly increased.
[0030] Example 6 HBA, HNA and GHB were copolymerized in a mass ratio of 70:30:5 to obtain pellet B. Pellets A and B were mixed and melt-spun to obtain blended LCP fibers. In order to ensure that the mass proportions of pellets A and B in this example are 60-70% and 40-30%, k = 2, N A = sin [π(t-15) / 30] + 13, N A Maintain at 12-14 rpm, N B = 20 -N A = -sin [π(t-15) / 30] + 7, N B The corresponding speed is 8-6 rpm, and the total speed N is constant at 20 rpm at the same time, with a cycle of 60 s. Take 2 g of the fiber sample, place it in 150 mL of DMSO solution, add 1 g of KOH solid, and stir at 30°C for 10 days to obtain a nanofiber suspension. After filtration, washing, and drying, blended LCP nanofibers are obtained with a diameter range of 50-70nm, a length range of 5-50 μm, and an aspect ratio range of 100-700. Compared with Example 5, the diameter and length of this example do not change significantly, and the aspect ratio increases slightly.
[0031] Example 7 HBA, HNA and GHB were copolymerized in a mass ratio of 70:30:5 to obtain pellet B. Pellets A and B were mixed and melt-spun to obtain blended LCP fibers. In order to ensure that the mass proportions of pellets A and B in this example are 70-80% and 30-20%, k = 3, N A = sin [π(t-15) / 30] + 15, N A Maintain at 14-16 rpm, N B = 20 -N A= -sin [π(t-15) / 30] + 5, N B The corresponding speed is 6-4 rpm, and the total speed N is constant at 20 rpm at the same time, with a cycle of 60 s. Take 2 g of the fiber sample, place it in 150 mL of DMSO solution, add 1 g of KOH solid, and stir at 30°C for 10 days to obtain a nanofiber suspension. After filtration, washing, and drying, blended LCP nanofibers are obtained with a diameter range of 30-50nm, a length range of 10-100 μm, and an aspect ratio range of 150-1000. Compared with Example 6, the diameter of this example is slightly reduced, but the length is significantly increased, and the aspect ratio is significantly increased.
[0032] Table 1 Relationship between the metering pump speed NA and NB and t function and the mass ratio of the pellets in Example 1-7
[0033] Table 2 Comparison of preparation methods and nanofiber product parameters between control example and example
Claims
1. A method for preparing polyarylate nanofibers, characterized in that: Here are the steps: (1) After HBA and HNA are acetylated, they are copolymerized with GHB to obtain HBA / GHB / HNA copolymerized aromatic ester, and pellet B is prepared; the acetylated HBA and HNA are copolymerized to obtain HBA / HNA copolymerized aromatic ester, and pellet A is prepared; wherein HBA is 4-hydroxybenzoic acid, HNA is 6-hydroxy-2-naphthoic acid, and GHB is 4-hydroxybutyric acid; (2) melt spinning the pellets A and B in step (1), respectively melting them through single screw extruder A and single screw extruder B, metering and conveying them through matching function numerical control metering pumps A and metering pumps B, and conveying melt A and melt B to a static mixer in a certain mass ratio, and after being fully mixed, extruding through a spinneret to obtain a blended polyarylate fiber; (3) placing the fibers spun in step (2) into dimethyl sulfoxide, adding solid potassium hydroxide, and stirring at a certain temperature for a certain period of time to obtain a polyarylate nanofiber suspension; (4) The suspension obtained in step (3) is filtered, washed with deionized water, and then placed in an oven for drying to finally obtain polyarylate nanofibers.
2. The method for preparing polyarylate nanofibers according to claim 1, characterized in that: In step (2), the sum of the speeds of the two metering pumps is the total speed N, which is constant at N = 20 rpm. The speeds of the two metering pumps are controlled by the function to change with the change of time seconds. The speed N of metering pump A is A = sin [π(t-15) / 30] + 9 + 2k, speed N of metering pump B B = N - N A = -sin [π(t-15) / 30] + 11 – 2k, t is the real time in seconds, k is a constant in revolutions per minute, which controls the speed N A and N B oscillation range.
3. The method for preparing polyarylate nanofibers according to claim 2, characterized in that: The speed of the metering pump in step (2) is N A , N B The range of is determined by the k value, which is 1-3, and the k value of the two functions is the same. t is the number of seconds of real time that keeps changing. The period of the two function relationships is 60 s. N = 20 rpm = N A + N B .
4. The method for preparing polyarylate nanofibers according to claim 1, characterized in that: In step (2), the mass ratio of pellets A and B is a variable, which is determined by N A and N B Direct control, mass proportion of pellet A or B = (N A or N B / N)×100%, the sum of the mass proportions of the two types of pellets is constant at 100%.
5. The method for preparing polyarylate nanofibers according to claim 1, characterized in that: In step (1), when pellet A is prepared, the mass ratio of each component is HBA: HNA = 7:
3. When pellet B is prepared by copolymerization, the mass ratio of each component is HBA: HNA: GHB = 70: 30: (1-5).
6. The method for preparing polyarylate nanofibers according to claim 1, characterized in that: In step (3), the corresponding relationship between the blended polyarylate fiber and the dimethyl sulfoxide-potassium hydroxide etching system is 150 mL of dimethyl sulfoxide and 1 g of potassium hydroxide solid for every 2 g of fiber, the temperature is 20-40°C, and the stirring time is 8-12 days.
7. The method for preparing polyarylate nanofibers according to claim 1, characterized in that: The polyarylate nanofibers obtained in step (4) present a uniform rigid rod-like structure with a diameter ranging from 50 to 500 nm, a length ranging from 1 to 100 μm, and an aspect ratio ranging from 30 to 1000.
8. The method for preparing polyarylate nanofibers according to claim 1, characterized in that: A polyarylate nanofiber is prepared by the preparation method described in any one of claims 1 to 6.
Citation Information
Patent Citations
Method for preparing aramid nanofibers based on deprotonation of Kevlar and nanofiber prepared thereby
CN112878036A
Method for improving performance of organic-inorganic composite material
CN112981931A
Preparation method of aramid nanofiber based on ball-milling-assisted deprotonation
CN115110306A
Liquid crystal polyarylester polymer, liquid crystal polyarylester fiber and preparation method
CN119081088A
Cited By
Preparation method of nanoscale liquid crystal polyarylester fiber
CN120401060A
A method for preparing nanoscale liquid crystal polyarylate fibers
CN120401060B